A model for examining middle school students' STEM integration behavior in a national technology competition - Chih-Jung Ku; Ying-Shao Hsu; Mei-Chen Chang; Kuen-Yi Lin (SpringerOpen, 2022)
Abstract Background Research on teaching and learning for science, technology, engineering, and mathematics (STEM) subjects has increased, and has demonstrated the importance of integrating interdisciplinary knowledge and skills. Our research model was based on the theory of planned behavior (TPB) and the data were analyzed by partial least squares-structural equation modeling. The present study aims to identify factors that play an important role in students' ability to integrate STEM knowledge and skills. Results Data were collected from participants who had won awards in local contests and represented their regions in a national technology competition. The reliability and validity of our instrument, the Students' STEM Integration Scale, were verified. The findings demonstrated that students' intentions to integrate STEM knowledge and skills to solve complex problems can be predicted by their attitude and perceived behavioral control. Conclusions This work highlights factors which are associated with students' intentions to integrate interdisciplinary knowledge and skills, and serves as a reference for research on the gap between intentions and actual behavior. The findings could help teachers and instructors design STEM-based activities to enhance students' attitudes, perceived behavioral control, and intentions, to improve their ability to integrate STEM knowledge and skills.